Graduate study in psychology - American Psychological Association ([Washington] American Psychological Association., 2002)
Descriptions of graduate programs in psychology in the United States and Canada. Accreditation by American Psychological Association is indicated when it applies. Entries are arranged alphabetically under states for the United States and alphabetically by institutions for Canada. Each entry gives information about the school, program, degrees offered, application, admission requirements, student statistics, tuition, financial assistance, minority considerations, and miscellaneous. Includes chart of fields of study and degrees offered. Institution index. 13th ed., 1980-1981, over 500 programs.
Keywords: Psychology; Education, Graduate -- North America; Psychology -- North America; Psychology--Study and teaching--Periodicals.